Insight on the reduction of copper content in slags produced from the Ausmelt Converting Process - Yuan H.-B.; Cai B.; Song X.-C.; Tang D.-Z.; Yang B. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The reduction of copper content in converting slag using process control is significant to copper smelter. In this study, the slags produced from the Ausmelt Converting Process for copper matte was analyzed using X-ray diffraction and chemical analysis. Thermodynamic calculation and effects of various conditions including the lance submerging depth in molten bath, the molten bath temperature, the addition of copper matte, and airflow rate were carried out to lower the content in the slag. Thermodynamic analysis indicated that the decrease of copper content was achieved by reducing Fe3O4, CuFe2O4, and Cu2O in the slag, decreasing the magnetism of slag and lowering the viscosity of slag, which was feasible at the operating temperature of the molten bath. Experiments showed that the optimal combination of operating conditions were found to be the addition of copper matte between 5,000 – 7,000 kg/h, a lance airflow rate of 13,000-14,000 Nm3/h, and a lance submergence depth into the molten bath of 700-900 mm, in which the copper content in the slag was effectively reduced from 22.74 wt. % to 7.70 wt. %. This study provides a theoretical support and technical guidance for promoting the utilization of slags from the Ausmelt Converting Process.